The Right to Bail in Extradition Proceedings: Malaysia's Criminal Law Perspective - Faizul Aswad Masri; Rohaida Nordin; Muhamad Helmi Md Said (Faculty of Law, Sriwijaya University, Indonesia, 2025)
This article delves into the issue of bail pending extradition in Malaysia. It adopts a doctrinal legal research methodology, focusing on analysing legislation and court decisions to objectively understand how current laws and practices determine bail applications within the context of Malaysian extradition law. The study reveals that Malaysia's Extradition Act 1992 does not explicitly provide for bail pending extradition, except under limited circumstances. Malaysian courts have utilised section 44 of the Extradition Act 1992 to apply bail provisions from the Criminal Procedure Code. The study finds that Malaysian courts adopt a cautious approach when determining bail applications in extradition cases. However, this judicial approach presents challenges, particularly in extradition cases involving offences governed by specific statutes other than the Criminal Procedure Code. The findings suggest that the reliance on section 44 should be re-evaluated to address these challenges. The article concludes by recommending further research to assess the need for an explicit and comprehensive provision for bail in the Extradition Act 1992 to ensure legal consistency and a uniform application across all types of offences.